2009
DOI: 10.1111/j.1524-4733.2009.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapse and Long-Acting Injectable Risperidone: A 1-Year Mirror Image Study with a National Claims Database in Taiwan

Abstract: This 1-year mirror-image analysis with claims-based data demonstrated that RLAI treatment was associated with reductions in relapses and hospital service utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Our results are consistent with many similar studies that seek to compare the efficacy of OA to LAI medications (Su et al, 2009;Gastpar et al, 2005;Kishimoto et al, 2013;Vincent et al, 2017). The reduction seen in the total number of MH ER visits (~48.6%) is consistent with other studies which have previously documented decreases between ~36% and 73% (Su et al, 2009;Denham & Adamson, 1971;Schooler, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our results are consistent with many similar studies that seek to compare the efficacy of OA to LAI medications (Su et al, 2009;Gastpar et al, 2005;Kishimoto et al, 2013;Vincent et al, 2017). The reduction seen in the total number of MH ER visits (~48.6%) is consistent with other studies which have previously documented decreases between ~36% and 73% (Su et al, 2009;Denham & Adamson, 1971;Schooler, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…The reduction seen in the total number of MH ER visits (~48.6%) is consistent with other studies which have previously documented decreases between ~36% and 73% (Su et al, 2009;Denham & Adamson, 1971;Schooler, 2003). However, in contrast to our results, randomized controlled trials (RCTs) have generally not found statistically significant differences between the efficacy of OA and LAI regimens (Kishimoto et al, 2012;Ostuzzi et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations